2011
DOI: 10.1021/ef2014265
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Stabilizing Agents for Water-in-Oil Emulsions

Abstract: The mechanism and ability to stabilize water-in-oil (w/o) emulsions have been compared for different emulsifiers, including asphaltenes extracted from a crude oil sample, hydrophobic silica particles, and a model acidic surfactant, N-(1-hexylheptyl)-N 0 -(5-carbonylicpentyl)perylene-3,4,9,10-tetracarboxylic bisimide (C5Pe). The results indicated that C5Pe describes the behavior of asphaltenes relatively well, although the interfacial activity was substantially higher than for the real asphaltenes at high pH. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…Using these systems and methodology it was shown that the stability of asphaltene- The stability of asphaltene emulsions also depends on the pH of the aqueous phase 31,101 . These emulsions exhibit a minimum stability at intermediate pH, while the stability is higher at low and high pH.…”
Section: Asphaltenes As Stabilizersmentioning
confidence: 99%
See 4 more Smart Citations
“…Using these systems and methodology it was shown that the stability of asphaltene- The stability of asphaltene emulsions also depends on the pH of the aqueous phase 31,101 . These emulsions exhibit a minimum stability at intermediate pH, while the stability is higher at low and high pH.…”
Section: Asphaltenes As Stabilizersmentioning
confidence: 99%
“…The emulsion stabilisation properties of perylene-based compounds were studied first by Nordgård et al 30 and then by Nenningsland et al 31 .…”
Section: Model Compounds As Stabilizersmentioning
confidence: 99%
See 3 more Smart Citations